Qualitative Study of Profit Margin Determinants and Pricing Practices: An Islamic Banking Perspective - Fauzias Mat Nor; Amir Shaharuddin; Norhaziah Nawai; Ainulashikin Marzuki; W Zainuddin Wan Abdullah (UUM Press, 2024)
Volume: 13 No: 2